IMPLEMENTASI MODUL MARKERLESS TRACKING PADA PENGENALAN SISTEM PENCERNAAN - Geofanny, Tya Agnesya; Hikmatyar, Missi; Sundari, Shinta Siti (JEIS: Jurnal Elektro dan Informatika Swadharma, 2024)
The age of technology cannot be denied that education also presents technology in learning. There are problems in the conventional learning process, where teachers tend to be active while students tend to be passive as seen from the results of student exams which on average get scores in the "enough" category. Augmented Reality can help learning to be interactive to help students increase interest in learning. Augmented Reality is designed based on Android mobile with Markerless Tracking method to make it easier for students to use the application anywhere and anytime, or when learning takes place because it does not require markers to run the application. Of the two learning methods that are conventional(non-treatment) and using AR applications(treatment) can be done experiments and comparisons of their effectiveness. Experiments were conducted with 5th grade students of SDN 1 Gunungcupu with the same material, quiz, and time criteria. In the comparison of the two methods carried out with non-treatment is influenced by treatment, and the results show that the percentage comparison of learning testing from both methods is (68.3%) where with non-treatment experiencing a far comparison with treatment. Based on the results that learning using AR applications in learning affects the effectiveness of student learning.Zaman yang serba teknologi tidak bisa dipungkiri pendidikan ikut menghadirkan teknologi dalam pembelajaran. Adanya permasalahan dalam proses belajar secara konvensional, dimana guru cenderung aktif sedangkan siswa cenderung pasif dilihat dari hasil ujian siswa yang rata-rata mendapat nilai dengan kategori â€œcukupâ€. Augmented Reality dapat membantu pembelajaran menjadi interaktif untuk membantu siswa meningkatkan minat belajar. Augmented Reality dirancang berbasis mobile Android dengan metode Markerless Tracking untuk mempermudah siswa dalam menggunakan aplikasi dimanapun dan kapanpun, atau saat pembelajaran berlangsung karena tidak membutuhkan marker untuk menjalankan aplikasi. Dari kedua metode pembelajaran yaitu secara konvensional (non treatment) dan menggunakan aplikasi AR (treatment) dapat dilakukan eksperimen dan perbandingan keefektifannya. Eksperimen dilakukan kepada siswa kelas 5 SDN 1 Gunungcupu untuk materi sistem pencernaan dengan kriteria materi, dan kuis yang sama. Dalam perbandingan kedua metode dilakukan dengan non treatment dan menggunakan treatment. Hasil menunjukkan bahwa persentase perbandingan pengujian pembelajaran dari kedua metode yaitu (68,3%) dimana dengan treatment hasilnya jauh lebih baik dari non treatment. Hal ini menunjukan bahwa pembelajaran menggunakan aplikasi AR dalam pembelajaran mempengaruhi keefektifan belajar siswa.